Global warming - Ernesto, Zedillo Ponce de LeoÌn (Center for the Study of Globalization, Yale University, 2008)
Ebook from IG Library; Includes bibliographical references and indexes; Introduction / Ernest Zedillo -- The IPCC : establishing the evidence / R.K. Pachauri -- Is the global warming alarm founded on fact? / Richard S. Lindzen -- Anthropogenic climate change : revisiting the facts / Stefan Rahmstorf -- "Dangerous" climate change : key vulnerabilities / Stephen H. Schneider -- The policy implications of climate change impacts / Robert Mendelsohn -- Economic analyses of the Kyoto Protocol : is there life after Kyoto? / William D. Nordhaus -- The European emissions trading regime and the future of Kyoto / Gernot Klepper and Sonja Peterson -- Climate change : designing an effective response / Thomas Heller -- An international policy architecture for the post-Kyoto era / Robert N. Stavins -- Controversies of Russian climate policy and opportunities for greenhouse gas reduction / Alexander Golub -- Climate policy in the United Kingdom / Howard Dalton -- Canada's approach to tackling climate change / John M.R. Stone -- India and climate change : mitigation, adaptation, and a way forward / Jvoti Parikh -- Correct choices for China : energy conservation, a cyclic economy, and a conservation-minded society / Shen Longhai